2008
DOI: 10.1128/jcm.01729-07
|View full text |Cite
|
Sign up to set email alerts
|

Early Impairment of Gut Function and Gut Flora Supporting a Role for Alteration of Gastrointestinal Mucosa in Human Immunodeficiency Virus Pathogenesis

Abstract: Our results show that impairment of the gastrointestinal tracts in human immunodeficiency virus (HIV)-positive patients is present in the early phases of HIV disease. This impairment is associated with alterations in gut microbiota and intestinal inflammatory parameters. These findings support the hypothesis that alterations at the gastrointestinal-tract level are a key factor in HIV pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 17 publications
10
162
4
4
Order By: Relevance
“…Pathogenic SIV as well as HIV infection results in rapid and significant Th17 loss from the GALT which would be expected to have deleterious effects on the regulation of microbial translocation (Brenchley, Schacker et al, 2004;Raffatellu, Santos et al, 2008). Indeed, HIV infection is correlated with increases in microbial translocation and mucosal inflammation (Gori, Tincati et al, 2008). This is supported by studies showing that plasma LPS levels, considered as an indication of microbial translocation, in HIV infected individuals are remarkably higher than uninfected individuals (Jiang, Lederman et al, 2009;d'Ettorre, Paiardini et al, 2011).…”
Section: Th17 Cells and Hiv Infectionsupporting
confidence: 69%
“…Pathogenic SIV as well as HIV infection results in rapid and significant Th17 loss from the GALT which would be expected to have deleterious effects on the regulation of microbial translocation (Brenchley, Schacker et al, 2004;Raffatellu, Santos et al, 2008). Indeed, HIV infection is correlated with increases in microbial translocation and mucosal inflammation (Gori, Tincati et al, 2008). This is supported by studies showing that plasma LPS levels, considered as an indication of microbial translocation, in HIV infected individuals are remarkably higher than uninfected individuals (Jiang, Lederman et al, 2009;d'Ettorre, Paiardini et al, 2011).…”
Section: Th17 Cells and Hiv Infectionsupporting
confidence: 69%
“…Altered stool composition has also been reported, with increased levels of fecal calprotectin, which is secreted by recruited neutrophils in the intestinal lining and has been proposed to be a marker of intestinal inflammation (103). Taken together, these data demonstrate a substantial subversion of physiological gut microbiome and a correlation between pathogenic intestinal flora and gut inflammation in HIV disease (102). In a recent study, Ellis et al (64) explored the intriguing hypothesis that the gut microflora composition affects both local and systemic immunity, in analogy with what was described in several clinical settings (104,105).…”
Section: Characterization Of Stool Microbes and Translocating Flora Isupporting
confidence: 54%
“…Interestingly, Gori et al demonstrated that HIV-infected individuals in early stages of disease are characterized by an impaired fecal flora, with a predominance of opportunistic pathogens (Pseudomonas aeruginosa and Candida albicans) and low levels of protective bacteria (bifidobacteria and lactobacilli) compared with historical data on healthy HIV-uninfected persons (102). Altered stool composition has also been reported, with increased levels of fecal calprotectin, which is secreted by recruited neutrophils in the intestinal lining and has been proposed to be a marker of intestinal inflammation (103).…”
Section: Characterization Of Stool Microbes and Translocating Flora Imentioning
confidence: 99%
“…LPS, which is a major structural component of the outer wall of Gram-negative bacteria and an effective CD14/TLR4 trigger, has been shown to be gradually increased in peripheral blood with the disease progression in HIV-1-infected subjects (19,(44)(45)(46)(47)(48). Because LY6E is upregulated during HIV-1 infection and plays a regulatory role in monocytes through modulating the expression of CD14, the innate immune responses to LPS stimulation in monocytes are likely to be attenuated via downregulating CD14/TLR4 pathway, as shown in our data ex vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%